Asymmetric Alkylation of Cyclic Ketones with Dehydroalanine via H‐Bond‐Directing Enamine Catalysis: Straightforward Access to Enantiopure Unnatural α‐Amino Acids. Issue 57 (18th August 2022) - Retini, Michele; Bartolucci, Silvia; Bartoccini, Francesca; Piersanti, Giovanni
Abstract: The growing importance of structurally diverse and functionalized enantiomerically pure unnatural amino acids in the design of drugs, including peptides, has stimulated the development of new synthetic methods. This study reports the challenging direct asymmetric alkylation of cyclic ketones with dehydroalanine derivatives via a conjugate addition reaction for the synthesis of enantiopure ketone‐based α‐unnatural amino acids. The key to success was the design of a bifunctional primary amine‐thiourea catalyst that combines H‐bond‐directing activation and enamine catalysis. The simultaneous dual activation of the two relatively unreactive partners, confirmed by mass spectrometry studies, results in high reactivity while securing high levels of stereocontrol. A broad substrate scope is accompanied by versatile downstream chemical modifications. The mild reaction conditions and consistently excellent enantioselectivities (>95 % ee in most cases) render this protocol highly practical for the rapid construction of valuable noncanonical enantiopure α‐amino‐acid building blocks. Abstract : A direct, highly enantioselective organocatalytic alkylation of cyclic ketones with dehydroalanine via a conjugate addition reaction is reported. The use of a chiral bifunctional primary amine/thiourea catalyst was key to obtain the enantiopure, functionalized (substituted ketone) unnatural α‐amino acids in good yields and remarkable selectivity. The mechanism of the reactions was explored by mass spectrometry studies.